Centro de Farmacovigilância do Ceará : análise do perfil de reação adversa a medicamento e queixa técnica - Francelino, Eudiana Vale (2007)
Drugs are the mainly therapeutical tool to the recoverying or maintenance of the population health condiction. Among the most common problems related for it are Adverse Drug Reactions (ADR) and Technical Complains (TC), being need this survey through the management, and development of activities of pharmacovigillance with the creation of helper’s and notifiers centers. Evaluate the ADR and TC sended to and analized by the pharmacovigillance center of ceara during its nine years of function toward to public health and rational use of drugs. Were collected All the ADR and TC notifications in the database of CEFACE, during the period of January 1997 to December 2005, being analized the following variables: gender and age, origin of the notification, notifier, drug involved, ADR, causality and severity classification of these ones and the kind of ADR according to Rawlins and Thompson. About the TC, the variables being: origin of notification, kind of TC, notifier, and drug or medical material involved. Also A research was made to identify in literature the possibility of pharmaceutical excipients being risks factors to cause ADR, using as initial data the 11 drugs most sold in the brazilian market in the period of November/02 to November/03 and their respective compositions. Lately was made the retrieve of cases with the involvement of these excipients in studies of suspects clinical cases. In the analized period, January 1997 to December 2005, the CEFACE registered 1.293 notifications. Of these ones, 1.172 (90,6%) ADR cases and 121 (9,4%) TC. There was a significant reduction of the number of notification during the years. Most of the ADR were registered in females (62,7%) and age of 21-30 anos (17,7%). Active search was the greatest notification method (59,3%). 85,6% (ADR) came from in hospitals with a percentual of publics in 81,6%. The therapeutical group with greatest involvement most was antibiotics for systemic use (40,0%). %). The skin system (48,5%) to be detached inside of the reported ADR. For causality, the higher number of ADR were classified as probably (44,1%) and for severity the highest percentual were considered as moderate (52,2%). Most were ADR A type. The severe and fatal ADR also occurred. The TC came from in hospitals (n=120), with emphasis to changing of color (47,1%) and lack of effectiveness (22,3%). In the literature were identified 10 risk pharmaceutical excipients, being 03 responsible for ADR collected in CEFACE database. The study of ADR and TC, as well as the establishment of their conditioners factors by a pharmacovigillance center, has large importance in public health and rational use of drugs context. Both the professional notifier and the population must be encouraged to notify all the suspects of ADR and TC to the responsable groups to be taken administrative measures among them: a) retrieve of inapropriated products from market; b) change in the labels and c) restriction in the use by population. The research in scientific literature shows in a clear way that, the involvment of excipients is a risk factor to ADR occurrence, enabling your insertion in the causality study of suspects cases.